2023
DOI: 10.3390/jcm12020661
|View full text |Cite
|
Sign up to set email alerts
|

Association between Experimental Pain Measurements and the Central Sensitization Inventory in Patients at Least 3 Months after COVID-19 Infection: A Cross-Sectional Pilot Study

Abstract: Fatigue, pain, headache, brain fog, anosmia, ageusia, mood symptoms, and sleep disorders are symptoms commonly experienced by people with post-COVID-19 condition. These symptoms could be considered as manifestations of central sensitization. The aim of this study is to evaluate whether there are indicators of central sensitization by using experimental pain measurements and to determine their association with patient-reported outcome measures (PROMs). A cross-sectional study including 42 patients after COVID-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 54 publications
0
1
0
Order By: Relevance
“…The presence of sensitization-associated symptoms in patients with post-COVID pain has been previously observed [19][20][21]. In fact, it has been previously suggested that some individuals with post-COVID pain can exhibit nociplastic features and may require a more nuanced multimodal treatment approach to achieve better treatment outcomes [42].…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…The presence of sensitization-associated symptoms in patients with post-COVID pain has been previously observed [19][20][21]. In fact, it has been previously suggested that some individuals with post-COVID pain can exhibit nociplastic features and may require a more nuanced multimodal treatment approach to achieve better treatment outcomes [42].…”
Section: Discussionmentioning
confidence: 93%
“…Some studies have identified the presence of sensitization-associated symptoms, assessed by Central Sensitization Inventory (CSI), in a range between 30% [19] and 70% [20] of patients with post-COVID pain. A recent pilot study identified the presence of a deficient conditioned pain modulation (CPM) in almost 15% of patients with post-COVID pain [21]. Identification of risk factors associated with sensitization-associated symptoms in individuals with post-COVID pain could help more personalized interventions.…”
Section: Introductionmentioning
confidence: 99%
“…Fatigue, pain, headache, brain fog, mood and sleep disorders, among others, are symptoms commonly experienced in post-COVID-19 patients. These symptoms could be considered as manifestations of central sensitization [111]. In fact, fatigue is one of the core symptoms in central-sensitizationassociated disorders [112], leading to the hypothesis that central sensitization might be an underlying common etiology in chronic pain patients and in patients with post-COVID-19 condition [113].…”
Section: Relationship Between Melatonin and Cortisol In Fibromyalgia ...mentioning
confidence: 99%
“…Different studies have reported a heterogeneous location of post-COVID pain, with a prevalence of 20-25% for widespread distribution [12][13][14]. The presence of widespread pain is associated with altered nociceptive processing, which has been recently identified in individuals with post-COVID pain [15].…”
Section: Introductionmentioning
confidence: 98%